Climate Zones of the Asphalt Binder Performance for the Highway Pavement Design - Ghassan Mohammed Ali Hussain; Mohammed Ahmed Ghaleb Abdulaziz; Zheng Nan Xiang; Mohammed A. Al-Hammadi (Civil Engineering Journal, 2020)
The asphalt pavement is exposed to the natural environment, which is affected by Climate change such as temperature, rain, ultraviolet, and other environmental conditions. This study aimed to establish the asphalt binder performance of Yemen so that the asphalt pavement can be designed to resist the distresses of rutting and cracking that occurred due to seasonal temperature changes and rainfall. The first step of determining the binder performance is to establish high and low temperatures, as well as rainfall because the asphalt binder is a temperature and rainfall sensitive viscoelastic material. To study the climatic zoning of asphalt pavement in Yemen, the data of temperature and rainfall in 19 provinces of Yemen in the past 10 years were collected and comprehensively analyzed, and the variations laws of them were analyzed. According to the Chinese approach, the climatic zoning of Yemen's asphalt pavement was divided. The moisture temperature coefficient was introduced, and its probability distribution state was also analyzed. The standard of the moisture temperature coefficient was suggested and the asphalt pavement climate zones based on the moisture temperature coefficient were determined. The results indicated that the main influencing factors of asphalt pavement in Yemen were the temperature rise and rainfall, and the climate zones of asphalt pavement were divided into different zones such as 1-2-1, 2-2-2, 1-2-2, and 3-1-2. According to the principle of equal probability, the moisture temperature coefficient was found to be 18, and the asphalt pavement climate zoning map was drawn. The findings of this study are highly significant and provide valuable decision support for pavement management and improve the transportation system. Doi: 10.28991/cej-2020-03091613 Full Text: PDF